The effects of trust and interdependence on relationship commitment: A trans-Atlantic study - GEYSKENS, Inge (Institutional Knowledge at Singapore Management University, 1996)
In recent years, interorganizational relationship management has become of paramount interest in marketing channels research. Marketing managers and researchers have identified mutual commitment among exchange partners in a marketing channel as central to successful relationship marketing and as key to producing significant benefits for firms. We consider two types of commitment that may characterize interfirm relationships. Affective commitment expresses the extent to which channel members like to maintain their relationship with specific partners. Calculative commitment measures the degree to which channel members experience the need to maintain a relationship. After conceptualizing commitment, we offer a set of hypotheses concerning the joint impact of trust and interdependence on both affective and calculative commitment. Testing our hypotheses in a field study involving two countries, we find strong evidence that total interdependence enhances both affective and calculative commitment. Which type of commitment develops depends on trust. The unexpected positive effect of interdependence asymmetry on affective commitment seems to be in line with a stream of research that has emphasized the positive role of power differences in promoting the effective coordination of channel relationships.